Characteristics Biomass for Raw Materials Pyrolysis Reactor - Ben Yudha Satria; Roy Firman Adventus Pasaribu; Hamid Asyraf Adani; Ari Susandy Sanjaya (Seminar Nasional Teknik Kimia Kejuangan, 2016)
Fibers, shells, and empty bunch is a waste of processing from palm oil mill that is still rarely used. During this time, palm oil is widely used as a vegetable oil without trying to discover the potential of palm oil waste. The purpose of this research was to look for characteristics that are appropriate for biomass pyrolysis reactor. The initial activities is to collect samples of biomass (fiber, shells, and empty bunch), and then mashed biomass. Biomass was analyzed by proximate test and calorific value by standard ISO 2009. Proximate testing includes testing moisture content, ash content, volatile matter and fixed carbon. Result of the research showed empty bunch is better than fibers and shells to be a raw material of pyrolysis reactor with calorific value 4.250 cal/g, volatile matter is 69,19 %. And fixed carbon is 13,65 %.